PENGARUH COUNTRY OF ORIGIN DAN BRAND IMAGE TERHADAP MINAT BELI PADA PRODUK SMARTPHONE SAMSUNG (Studi Pada PT Samsung Electronic Indonesia Cabang Pekanbaru) - Nurul Annisa; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of Country Of Origin and Brand Image on Interest Buy on Samsung Smartphone Products (Study At PT Samsung Elektronic Indonesia Branch Pekanbaru). Country Of Origin is a person's view of a product from the country of origin of the product concerned. Brand Image is one important part in the company because the attitude and actions of consumers against a company brand is determined by the brand image of the company. Country of origin and brand image can have an impact on buying interest. With the influence of country of origin and brand image of buying interest then the product from the country of origin and have a brand image so that consumer buying interest appears. This research was conducted at PT Samsung Elektronic Indonesia Pekanbaru Branch. This study took the number of respondents ie 100 people.Data obtained through questionnaires. The data from the questionnaire is further processed using statistical analysis that is simple linear analysis, multiple linear analysis, determination analysis, and significance test with t test (partial), F (simultaneous) test.The results showed that the test results of the first t test hypothesis that is country of origin to buy interest is tcount (19.249)> ttabel (1,984) means country of origin significant effect on buying interest. Both brand image of buying interest is titung (9,982)> ttable (1,984) meaning there is significant influence between brand image to consumer buying interest. F test results of country of origin and brand image of buying interest are F arithmetic (203,142)> F table (3.090). This means that the country of origin and brand image simultaneously significantly influence consumer buying interest.Keywords: Country Of Origin, Brand Image, Buying Interest